Методичні та технічні аспекти реалізації онлайн лабораторії з проектування пристроїв - Семенець, В. В.; Свид, І. В.; Зубков, О. В.; Воргуль, О. В.; Бойко, Н. В.; Чумак, В. С. (ХНУРЕ, 2020)
Technical and methodological aspects of implementation of online laboratory for designing devices on microcontrollers and programmable logic integrated circuits are considered. One of the options for implementing an online laboratory is considered. This solution allows you to comply with quarantine measures and ensure the quality of the educational process.
Keywords: вища освіта; технічна освіта; навчальна лабораторія; онлайн лабораторія; мікроконтролер; технічні аспекти